Penerapan Pendidikan Agama Kristen Berbasis Transformasi Spiritual Upaya Pengembangan Karakter dan Resiliensi Siswa Rentan Studi Kasus di SMP Harapan Arcawinara Bekasi - Tri Pudji Rahayu; Rode Sri Rahayu (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
No individual chooses to be born into a specific family or under certain conditions. Differences in socioeconomic conditions will always exist in society, leading to the formation of various groups at any time and place. When a teenager is born into a family with a different socioeconomic background, it can cause pressure due to feelings of inferiority, embarrassment, and even jealousy, as socioeconomic status impacts their life and education. Every child has the right to education. The cost of education is a challenge for those in vulnerable socioeconomic conditions. The issues they face are not just economic but also social in nature. Fostering Christ-like character should be a focus in Christian education, especially for adolescents. Adolescence is a vulnerable and complex stage with issues and conflicts related to self-image, values, ethics, and morality. Teenagers need proper guidance and teaching to grow into strong individuals with a Christ-like character and resilience in their lives. Economic issues are indeed related to education. However, there remains an open path to educate adolescents according to their needs. “Train up a child in the way he should go, and when he is old, he will not depart from it.” (Proverbs 22:6)